Dynamic presentations - Powell, Mark (Cambridge business skills., 2011)
Aimed at executives and those developing a career in business, this book looks at what constitutes a successful, motivating presentation and gives learners an insight into the essential skills and techniques they will need to ensure their presentations are both motivating and memorable.